Neural mechanisms of training an auditory event‐related potential task in a brain–computer interface context. Issue 8 (28th January 2019) - Halder, Sebastian; Leinfelder, Teresa; Schulz, Stefan M.; Kübler, Andrea
Abstract: Effective use of brain–computer interfaces (BCIs) typically requires training. Improved understanding of the neural mechanisms underlying BCI training will facilitate optimisation of BCIs. The current study examined the neural mechanisms related to training for electroencephalography (EEG)‐based communication with an auditory event‐related potential (ERP) BCI. Neural mechanisms of training in 10 healthy volunteers were assessed with functional magnetic resonance imaging (fMRI) during an auditory ERP‐based BCI task before ( t 1) and after ( t 5) three ERP‐BCI training sessions outside the fMRI scanner ( t 2, t 3, and t 4). Attended stimuli were contrasted with ignored stimuli in the first‐level fMRI data analysis ( t 1 and t 5); the training effect was verified using the EEG data ( t 2‐ t 4); and brain activation was contrasted before and after training in the second‐level fMRI data analysis ( t 1 vs. t 5). Training increased the communication speed from 2.9 bits/min ( t 2) to 4 bits/min ( t 4). Strong activation was found in the putamen, supplementary motor area (SMA), and superior temporal gyrus (STG) associated with attention to the stimuli. Training led to decreased activation in the superior frontal gyrus and stronger haemodynamic rebound in the STG and supramarginal gyrus. The neural mechanisms of ERP‐BCI training indicate improved stimulus perception and reduced mental workload. The ERP task used in the current study showed overlapping activations with a motor imagery based BCI task from a previous study on the neural mechanisms of BCI training in the SMA and putamen. This suggests commonalities between the neural mechanisms of training for both BCI paradigms.